Strategi Komunikasi L-Men terhadap Komunitas Affiliate L-Men Creator Crew dalam Meningkatkan Brand Awareness - Raden Roro Fatimah Azzahra Aulia; Hudi Santoso (Pusat Riset dan Inovasi Nasional, 2025)
This study examines the communication strategy of PT Nutrifood Indonesia through the L-Men Creator Crew (LCC) program as an implementation of the Integrated Marketing Communication (IMC) theory within the context of digital affiliate marketing. The research background stems from the shifting marketing landscape toward collaboration with content creators as a means to build authentic relationships and enhance brand awareness. The purpose of this study is to analyze how L-Men’s communication strategy is integrated across various IMC elements, including advertising, sales promotion, public relations, direct marketing, personal selling, and digital marketing. This research employs a descriptive qualitative approach, with data collected through observation, in-depth interviews, and documentation. The findings indicate that L-Men successfully established an effective two-way communication system with its affiliate community through a community-based approach, personalized guidance, and consistent promotional support. The integration of messages across digital channels creates synergy that strengthens the brand image as an active, inspiring, and relevant brand for the younger generation. The implications of this study emphasize the importance of implementing IMC that focuses on long-term relationships and community collaboration in contemporary digital communication strategies.